USING YOUTUBE VIDEO TO IMPROVE STUDENTSâ€™ VOCABULARY FOR 3RDÂ GRADERS IN ELEMENTARY SCHOOL - Destya Fitri Anggraeni; Agnes Widyaningrum (LINGUAMEDIA Journal, 2023)
ABSTRACTÂ Technology is developing rapidly in the field of education, requiring teachers to utilize technology to support the learning process in the classroom, which is an alternative to attracting students' interest in the learning process. This study aims to determine the effectiveness of YouTube videos as a learning medium to improve the vocabulary of grade 3 students at SDN 01 Trimulyo. Success in the learning process is inseparable from the teacher's role in organizing and managing the class and the various constraints that exist in the classroom. In this study, we used the Classroom Action Research (CAR) method. The stages of research are planning, action, observation, and reflection. The findings from this study indicate that the use of YouTube videos as a learning medium can increase students' vocabulary. The use of YouTube videos as a learning medium provides many benefits for students, one of which is making vocabulary easier for them to learn. In other words, YouTube videos are great media that can be used to teach vocabulary. The use of YouTube videos as a medium for learning English has a positive impact on increasing students' vocabulary mastery.